Hedonic Treadmill Analysis According to Hamka's Perspective in Tafsir Al-Azhar - Ngulwiyah, Istinganatul; Syihabudin, Syihabudin; Najmudin, Najmudin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
Many Indonesian people are currently trapped by the Hedonic Treadmill. The hedonic treadmill is a condition in which a person pursues happiness until he reaches endless satisfaction. Happiness depends on material things, they chase millions of treasures and pile up as if they never feel enough which causes a person to be trapped in pseudo-happiness. Islam guides every human being on how to acquire wealth and use it. Therefore it is very important to have a discussion about this from Hamka's point of view so that humans can be guided toward real life and happiness. The purpose of this research is to analyze and study the Hedonic Treadmill from Buya Hamka's perspective. The method used in this study is descriptive qualitative with content analysis techniques in the book Tafsir Al-Azhar by Buya Hamka, using QDA Minerlite software. The results of this study indicate that, according to Hamka, the hedonic treadmill is a human nature that is very attached to wealth, exaggerates and tends to justify any means to get it, always boasts about it to other humans, does not care about the negative aspects that wealth can cause, so that it can cover up logical reasoning. and distract them from the true purpose of their creation. Hamka has provided a solution for each individual to avoid and stay away from the hedonic treadmill, namely by taqarrub ila-Allah, doing good deeds, living Qanaah, and always being grateful for everything that has been given to him by Allah, and applying the attitude of Zuhud. exaggerates and tends to justify any means to get it, always boasts about it to other humans, and does not care about the negative aspects that wealth can cause, so that it can cover up logical reasoning. and distract them from the true purpose of their creation. Hamka has provided a solution for each individual to avoid and stay away from the hedonic treadmill, namely by taqarrub ila-Allah, doing good deeds, living Qanaah, and always being grateful for everything that has been given to him by Allah, and applying the attitude of Zuhud. exaggerates and tends to justify any means to get it, always boasts about it to other humans, and does not care about the negative aspects that wealth can cause, so that it can cover up logical reasoning. and distract them from the true purpose of their creation. Hamka has provided a solution for each individual to avoid and stay away from the hedonic treadmill, namely by taqarrub ila-Allah, doing good deeds, living Qanaah, and always being grateful for everything that has been given to him by Allah, and applying the attitude of Zuhud.